The role of the Ina-SDI in supporting the development of the geospatial industry in Indonesia - Karsidi, ﻿Asep (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
﻿In the past, geospatial data and information systems were developed for a nation’s security purposes, but nowadays they are utilized to augment its prosperity. Accordingly, the development of geospatial information and communication infrastructure has become imperative to provide the ease and speed of geoinformation access, as well as to reduce redundancy. In this vein, the Indonesian government (GoI) has established the Ina- SDI (Indonesian GeoSpatial Data Infrastructure) under the Presidential Regulation Nr. 85 year 2007, following which the BAKOSURTANAL (National Coordinating Agency for Surveying and Mapping) received a mandate from the GoI to coordinate the development of Ina-SDI operational model which is to be actualised within two years under the Ina-SDI Development Project. This article embarks on an exploratory assessment of the development of Ina-SDI. The conclusion is that the success of the Ina-SDI is dependent on the completion of a nationwide standardized based map, the integration of all Ina-SDI geospatial data and information players, the support for ease and speed of data and information accessibilities through integrated ICT infrastructures, and the provision and enforcement of laws and regulation to enable the Ina-SDI to take off from a ‘rowing’ to a ‘steering’ role in order to lend support to the country’s geospatial commerce and industry.